Sistem Pendukung Keputusan Karyawan Magang Menjadi Karyawan Tetap Divisi Mekanik Menggunakan Metode AHP dan TOPSIS ( Studi Kasus di Raihan Motor) - Riko Pulanggeni; Paulus Harsadi; Kumaratih Sandradewi; Raden Arie Febrianto; Tri Irawati (Redtech Putra Benua, 2026)
The process of determining which interns are eligible for permanent appointment in the mechanics division at Raihan Motor is still conducted manually and subjectively, potentially leading to inconsistent decision-making. This study aims to develop a Decision Support System (DSS) that assists leaders in objectively and measurably determining the best interns. The Analytical Hierarchy Process (AHP) method is used to determine the importance weights of each assessment criterion, while the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method is used to rank alternative employees based on the criterion weights. The assessment criteria used include discipline, technical skills, responsibility, teamwork, and work ethic. The results of the study indicate that the system can provide recommendations for interns eligible for permanent appointment based on the highest preference value, thereby making the decision-making process more objective, effective, and consistent.